METHOD OF EVALUATION OF THE ELECTRIC FIELD LEVEL OF DANGEROUS SIGNALS TO GNSS RECEIVERS - Shvets, Valeriyan; Kharchenko, Volodymyr (Proceedings of National Aviation University (archive), 2018)
Purpose: It is necessary to develop and test a method for estimating the dangerous signals level to GNSS receivers in order to make a decision on the possibility of fulfilling the target function of the GNSS radio receiver under the influence of interference and to solve the navigation problem. Method: the approach is based on the analysis of the electromagnetic environment, the statistical criteria for optimal detection and instrumental measurements. Results: the article uses the basis of normative documents on the application of GNSS to propose a method for estimating the state of the electromagnetic environment at the location of the GNSS radio receiver in order to make a decision on the possibility of performing the target function by the radio receiver of navigation signals. The proposed method was tested at the National Aviation University. Discussion: the method is proposed for a tactical assessment of the electromagnetic situation at the location of the GNSS radio receiver and making a decision on whether the target function can be performed by this radio receiver.